Aqueous Mixtures of Deep Eutectic Solvents: Tuning the Reaction Medium and Photocatalyst for Highly Selective Amine Oxidation - Kare, Varsha S.; Tiwari, Shraeddha S. (Sustainability & Circularity NOW, 2025)
Harvesting light as a source of energy for driving chemical processes is an important aspect of tacking the looming energy crisis. The challenge lies in making the process sustainable while retaining the efficiency and selectivity. In this work, deep eutectic solvents and their aqueous mixtures are used to replace acetonitrile as the reaction medium for the photocatalyzed amine oxidation. It is observed that the use of deep eutectic solvents as reaction media leads to >90% conversion but presents issues with efficient workup due to high viscosity. The use of water a cosolvent mitigates the issue. Further modification of the catalyst surface with alizarin enables the use of higher water content (in a 1:1 ratio) and leads to high conversion (>90%) at one-tenth of irradiation intensity. The high yield and selectivity eliminate the need for tedious purification steps to isolate the product. Control experiments indicate cooperative contributions by TiO2, 2,2,6,6-tetramethylpiperidin-1-yl)oxyl (TEMPO), and alizarin as mechanistic factors responsible for the enhanced reactivity.
Keywords: Deep eutectic solvent; Aqueous mixture; Photocatalysis; Amine oxidation; Heterogeneous catalysis